2012
DOI: 10.1007/s00213-012-2683-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acupuncture on stress-induced relapse to cocaine-seeking in rats

Abstract: Rationale Cocaine addiction is associated with high rates of relapse, and stress has been identified as a major risk factor. We have previously demonstrated that acupuncture reduces drug self-administration and dopamine release in the nucleus accumbens (NAc), a brain structure implicated in stress-induced reinstatement of drug-seeking behavior. Objective This study was conducted to investigate the effects of acupuncture on footshock-induced reinstatement of cocaine-seeking and the expression of c-Fos and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
27
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 71 publications
5
27
1
Order By: Relevance
“…The effects of acupuncture on WMW tasks and CREB phosphorylation in the presence of a PKA inhibitor. that acupuncture inhibits pCREB activation in the nucleus accumbens [45] and spinal cord [46] in drug addiction. This result indicates that acupuncture produces different effects on the expression of pCREB in different parts of the body for different diseases, in accordance with the holistic view of acupuncture treatment in the TCM theory.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of acupuncture on WMW tasks and CREB phosphorylation in the presence of a PKA inhibitor. that acupuncture inhibits pCREB activation in the nucleus accumbens [45] and spinal cord [46] in drug addiction. This result indicates that acupuncture produces different effects on the expression of pCREB in different parts of the body for different diseases, in accordance with the holistic view of acupuncture treatment in the TCM theory.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of acupuncture on cocaine‐induced locomotor activity, expression of phospho‐cyclic AMP response elements binding (pCREB) and c‐Fos in the NAc, release of GABA in the VTA and DA in the NAc and cocaine‐seeking behavior were investigated by manual acupuncture at bilateral HT7 acupuncture points in freely moving animals, as performed previously in our laboratory (Zhao et al ; Yoon et al ). HT7 acupoint on the heart channel has been used to treat mental and psychiatric disorders in clinic of oriental medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Based on these findings, EA influences MAO-A expression maybe via regulating the inflammatory cytokines-related pathways. In addition, EA-related reduction in cocaine-induced behavioral sensitization is closely associated with the reduction of dopamine synthesis in the ventral tegmental area (VTA) region [17] and phosphorylated cAMP response element-binding protein expression in the NAc [8]. A study suggested that EA enhances extinction learning of heroin-induced seeking behavior, which may associate with cAMP downstream pathway—FosB expression in the NAc [40].…”
Section: Discussionmentioning
confidence: 99%
“…In 1979, the World Health Organization (WHO) provided a list of 40 diseases suitable for acupuncture treatment; these included heroin and cocaine dependence and abuse [7]. Some clinical and basic studies have suggested that acupuncture, as a therapeutic tool, is useful for reducing drug abuse-induced seeking behaviors and side effects by restoring cellular function imbalance in the central nervous system (CNS) [810]. Acupuncture at several specific acupoints could reduce cocaine-induced seizures, behavioral sensitization, stress-induced cocaine relapse, and METH-induced hyperactivity in rodent models [810].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation